2008
DOI: 10.1017/s1368980007001322
|View full text |Cite
|
Sign up to set email alerts
|

Association of antioxidant vitamins and oxidative stress levels in pregnancy with infant growth during the first year of life

Abstract: Objective: Whereas there are numerous reports in the literature relating the impact of maternal nutritional status on subsequent birth outcome, much less is known about the long-term impact on infant growth after birth. Therefore, we conducted a prospective cohort study to investigate the association of maternal micronutrient status (vitamins A, C and E, folate) and oxidative stress status in pregnancy with infant growth during the first year of life. Design: Prospective cohort study. Setting: Outpatient clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 43 publications
1
15
0
Order By: Relevance
“…Data on morbidity, mortality and growth of children whose mothers received vitamin C supplements during pregnancy are not available. One prospective cohort study of oxidative stress and antioxidant vitamin status in South Korea found that mothers in the highest quartile of vitamin C concentration at 24–28 weeks' gestation had infants with significantly greater weight and length at birth, 6 and 12 months after adjustment for confounders 123 …”
Section: Resultsmentioning
confidence: 99%
“…Data on morbidity, mortality and growth of children whose mothers received vitamin C supplements during pregnancy are not available. One prospective cohort study of oxidative stress and antioxidant vitamin status in South Korea found that mothers in the highest quartile of vitamin C concentration at 24–28 weeks' gestation had infants with significantly greater weight and length at birth, 6 and 12 months after adjustment for confounders 123 …”
Section: Resultsmentioning
confidence: 99%
“…So this confirms that the zinc is important in the development pre- and postnatal (41). In fact, the use of zinc supplements increases birth weight and decreases related pregnancy complications (42). …”
Section: Discussionmentioning
confidence: 99%
“…However, the beneficial effect of antenatal micronutrients supplementation on postnatal growth of children is still unclear. It was reported that children of mothers with higher levels of vitamin C during pregnancy may be taller and heavier at the age of 6 and 12 months [10]. In another study carried out in Indonesia, vitamin A supplementation among pregnant women improves child growth at certain periods in the first two years compared with the combined supplementation of zinc and vitamin A [11].…”
Section: Introductionmentioning
confidence: 99%